1997
DOI: 10.1002/cjce.5450750408
|View full text |Cite
|
Sign up to set email alerts
|

Gas permeation and isobutane dehydrogenation over very thinPd/ceramic membranes

Abstract: An attempt was made in this study to prepare very thin palladium membranes. Pd was electrolessly deposited on the inner side surface of a mesoporous ceramic tube using a peristaltic pump to circulate the electroless solution through the tube. To obtain defect-free Pd membranes, a two-step deposition procedure from a dilute Pd2' bath and a concentrated Pd2' bath was practised with great care to avoid the difficulties associated with the mismatch of thermal expansion coefficients between Pd and the ceramic subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…(b) Since Sn has a low melting point (505 K), it could be enhancing metallic diffusion along the grain boundaries, widening channels for the diffusion of gases. (c) The mismatch in the thermal expansion coefficient between Pd and alumina could result in film cracking or delamination. , (d) Residual porosity in the Pd film produced during electroless plating could easily transform into pores. We believe that all four of these processes play a role in the observed pore formation and selectivity decline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(b) Since Sn has a low melting point (505 K), it could be enhancing metallic diffusion along the grain boundaries, widening channels for the diffusion of gases. (c) The mismatch in the thermal expansion coefficient between Pd and alumina could result in film cracking or delamination. , (d) Residual porosity in the Pd film produced during electroless plating could easily transform into pores. We believe that all four of these processes play a role in the observed pore formation and selectivity decline.…”
Section: Resultsmentioning
confidence: 99%
“…Restoration of the permselectivity of membrane 11 upon lowering the temperature as discussed above may have been from the opening of diffusion paths because of stress induced by a mismatch in the thermal expansion coefficient, which then closed when the stress was relieved by returning to a lower temperature. Shu et al have attempted to alleviate this problem by forming the Pd film using two different plating baths which create different structures . The first bath deposits a more porous film in order to help absorb stress from a mismatch in the thermal expansion coefficient while the second bath deposits a denser, selective layer.…”
Section: Resultsmentioning
confidence: 99%
“…A temperature of 723 K was chosen because the experimental studies of isobutane dehydrogenation in a catalytic membrane reactor are normally performed at this temperature [3,[5][6][7]. Previous calculations of viscous flow over diffusion ratio [13] have shown that convective contribution to transport is negligible (less than 3% of the global flux).…”
Section: Membrane Defect Characterization Through Gas Permeations Andmentioning
confidence: 99%
“…Indeed continuous and selective hydrogen removal can either improve olefins yields, or allows lower operating temperatures for the same conversions. Experimental studies illustrating such an improvement on isobutane dehydrogenation have been reported [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, studies on dehydrogenations of alkanes and aromatic compounds have still received most attention (see e.g. those performed on Pd membranes: Gobina et al, 1995;Gobina and Hughes, 1996b;Sheintuch et al, 1997;Shu et al, 1997). Attention has also been paid to the steam-and CO -reforming of methane to syngas, led to high per-pass conversions by selective permeation of hydrogen through Pd}Ag membranes (Shu et al, 1995).…”
Section: Reactions and Reactorsmentioning
confidence: 99%